2014
DOI: 10.1530/rep-13-0588
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 during embryo implantation and its upregulation by oestradiol in mice

Abstract: Pregnancy requires successful implantation of an embryo, which occurs during a restricted period defined as 'receptivity of the endometrium' and is influenced by the ovarian steroids progesterone and oestradiol. The role of poly(ADP-ribose)polymerase-1 (PARP1) in apoptosis is well established. However, it is also involved in cell differentiation, proliferation and tissue remodelling. Previous studies have described the presence of PARP in the uterus, but its exact role in embryo implantation is not yet elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…5 ). Thus far, the vast majority of the studies examining the mechanisms that underlie implantation have focused on the communication events that occur between maternal cells and trophoblast cells 19 20 58 59 60 61 . Therefore, to the best of our knowledge, the findings reported here provide the first demonstrations that the embryo can send signals which directly promote trophoblast migration and influence the implantation process.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Thus far, the vast majority of the studies examining the mechanisms that underlie implantation have focused on the communication events that occur between maternal cells and trophoblast cells 19 20 58 59 60 61 . Therefore, to the best of our knowledge, the findings reported here provide the first demonstrations that the embryo can send signals which directly promote trophoblast migration and influence the implantation process.…”
Section: Discussionmentioning
confidence: 99%
“…PARP1 and PARP2 activation were shown to be a key step in the development of insulin resistance (for review, see Bai and Cantó 2012). Hormones, such as insulin (Horvath et al 2008), estrogens (Mabley et al 2005;Jog and Caricchio 2013;Joshi et al 2014), androgens (Shimizu et al 2013), progesterone (Ghabreau et al 2004), artificial steroids, and vitamin D (Marton et al 2018b) can modulate the expression and activity of PARP1 and PARP2. Endocrine disruptors were also shown to modulate PARP activity (Chen et al 2013;Guerriero et al 2018).…”
Section: Parps In Regulating Central and Peripheral Organismal Metabomentioning
confidence: 99%
“…Moreover, PARP-1 has also been reported to be involved in transcriptional regulation of SMAD3 [30], sex determining region Y-Box-2 [31] and E-cadherin [32], most of which are important factors for implantation of embryo. Joshi et al 2014 [33] demonstrated the role of PARP-1 in embryo implantation by preparing the uterus for it. Thus role of PARP-1 in embryonic development in our study cannot be ignored.…”
Section: Fig 5a Discussionmentioning
confidence: 99%